2019
DOI: 10.5137/1019-5149.jtn.24969-18.2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of thoracic disc herniation: anterior vs posterior approach

Abstract: AIM: To compare outcomes and complications in patients with thoracic disc herniation (TDH) undergoing surgery with either the posterior or anterior approach. MATERIAL and METHODS: A total of 86 patients, with 98 symptomatic TDHs, who underwent surgery in a single institution between 2007 and 2016, were included. Overall, 68 patients were in the anterior and 18 were in the posterior group. Ten patients underwent multilevel TDH surgery. RESULTS: The groups were similar in age, sex, body mass index, and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Surgical approach is mainly defined by the location of the neural compression, which is anterior in thoracic disc herniations-choosing a posterior approach does not target the lesion directly and carries an inherent risk of spinal cord manipulation. As such, an anterior approach is favored by some for large, calcified herniations and a posterior approach for smaller, uncalcified herniations, 15,20 as numerous studies have suggested that calcification of TDH may lead to intraoperative neurological injury, especially when the calcified disc occupies >40% of the spinal canal. 16,21 -23 In our study, it is possible that the higher rate of neural deficits was a result of posterior operations being used to treat large calcified discs paracentrally and/or centrally, which would lend support to the aforementioned recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical approach is mainly defined by the location of the neural compression, which is anterior in thoracic disc herniations-choosing a posterior approach does not target the lesion directly and carries an inherent risk of spinal cord manipulation. As such, an anterior approach is favored by some for large, calcified herniations and a posterior approach for smaller, uncalcified herniations, 15,20 as numerous studies have suggested that calcification of TDH may lead to intraoperative neurological injury, especially when the calcified disc occupies >40% of the spinal canal. 16,21 -23 In our study, it is possible that the higher rate of neural deficits was a result of posterior operations being used to treat large calcified discs paracentrally and/or centrally, which would lend support to the aforementioned recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusively, we should also note that although these novel techniques can result in favorable outcomes, complex cases such as migrated large calcified thoracic discs can be challenging. [3][4][5][6] The importance of training in full-endoscopic procedures should be emphasized, and these cases are likely best reserved for surgeons with sufficient clinical experience and volume in full-endoscopic spine procedures. 7…”
Section: :40 Visual Appreciation Of Discmentioning
confidence: 99%
“…Disk herniation represents a frequent disease, particularly affecting people aged 30 to 50 with an incidence of about 5 to 20 cases per 1000 adults annually [1]. While lumbar disk herniations are most frequently encountered, thoracic disk herniations are rare accounting for less than 1% of all cases [2][3][4][5]. However, thoracic disk herniations can result in miscellaneous clinical symptoms including severe myelopathy [4].…”
Section: Introductionmentioning
confidence: 99%
“…While lumbar disk herniations are most frequently encountered, thoracic disk herniations are rare accounting for less than 1% of all cases [2][3][4][5]. However, thoracic disk herniations can result in miscellaneous clinical symptoms including severe myelopathy [4]. Moreover, spinal nerve root impingement can cause severe pain and neurological symptoms.…”
Section: Introductionmentioning
confidence: 99%